TikTok as a Dermatology Education Medium: dr. Zie’s Personal Branding Strategy - Rizka Septiana; Tiara Dwi Tamara (Indonesian Journal Publisher, 2025)
The development of digital technology has transformed how individual communicate and construct their identities, including through self-branding strategies to increase visibility and enhance credibility in public spaces. In Indonesia’s skincare industry, the shift toward dermatology-based products has also introduced new challenges, particularly the rise of exaggerated claims and misinformation on social media. In this context, the presence of healthcare professionals who provide education content has become increasingly important. This study aims to analyse the communication strategies used the TikTok account @dr.ziee in building personal branding through skincare educational content, as well as assess how such content contributes to shaping a professional image in the eyes of the audience. Using a descriptive qualitative approach, this research examines communication patterns, message consistency, and the professional representation displayed by dr. Zie as an aesthetic doctor actively producing dermatology content in TikTok. The finding show that dr. Zie’s use of TikTok successfully established strong personal branding through consistent uploads, accurate science-based information, and friendly communication style. Analysis based on Montoya’s eight personal branding principles indicates that specialization is the most dominant element, reflected on her clear focus on skin-health education and the absence of promotional motives in her content. These findings affirm that TikTok functions not only as entertainment platform but also as a strategi medium for professionals to build legitimacy and public trust through credible educational communication